Intensidade constante ou ajustável de corrente elétrica não elicita diferentes níveis de fadiga do músculo quadríceps femoral durante sessões de estimulação elétrica neuromuscular em pacientes com doença pulmonar obstrutiva crônica leve-moderada - Rondelli, Rafaella Rezende (2008)
Introduction: Neuromuscular electrical stimulation (NMES) has been applied in patients with chronic pulmonary obstructive disease (COPD). Despite the intensity of electrical current may play an important role in improving strength, it has not changed during the same NMES session. Aim: to assess the muscle fatigue after two different modalities of NMES in patients with COPD. Method and Material: 22 COPD patients (FEV1 = 51.1±16.3% pred) were randomized to two protocols (one week apart) of NMES of the quadriceps femoris with: (i) constant intensity, which was set at the maximal tolerance and maintained for 40 minutes (Maximal tolerance intensity constant, MTIC), and (ii) adjustable intensity, which was initially set as described MTIC, but it was incresead after five minutes of session and maintained for additional 35 minutes (Maximal tolerance intensity adjustable, MTIA). Surface electromyographic was used to analyse quadriceps femoris fatigue (median frequency: MF - Hz and root mean square: RMS - V) during 40% of maximal voluntary contraction pre and post-NMES sessions. Results: The intensity level in MTIA protocol was significantly higher than the MTIC (34.53±11.35 mA vs 36.22±10.41 mA, p <0.05). However, this difference was not enough to elicit difference in fatigue between modalities. For both constant and adjustable intensities, MF reduced (75.287.12 to 70.086.63 and 72.369.98 to 69.289.15, p < 0.05, respectively) and the RMS increased (53.6723.68 to 64.2028.70 and 59.0528.65 to 64.0028.49, p < 0.05, respectively). However, no difference was observed at fatigue between MTIC and MTIA. Conclusion: The only one adjustment during the same NMES session is not able to recruit more motor units, hence it was observed the same fatigue level between protocols.